Main factors influencing floral differentiation and fruit establishment in squash (Cucurbita spp.) = Principales factores que influyen en la diferenciación floral y el cuaje de frutos en zapallo (Cucurbita spp.) - Della Gaspera, Pedro; Portela, Jose Antonio (Asociación Argentina de Horticultura, 2021)
Different agronomic practices can be implemented to increase productivity in squashes (Cucurbita spp.), although they do not always render the same results. They depend on environmental factors such as temperature, environmental humidity, water quality as well as nutrient availability in the soil, which among other variables influence maturation precocity, culinary quality and fruit preservation capacity. In this context, it is relevant to know the way in which flowering and fruit settling are being influenced, in order to understand which conditions are determining the best performance in yield, quality as well as fruit conservation. There is a lot of information about these factors, but it is scattered, which makes it difficult to answer questions that may arise about the influence of the genetic basis and the environment, as well as the hormonal processes in response to the signals of the latter. The objective of this literature review is to update the available information on the factors that influence the processes of flowering and establishment of the squash fruits, and to extract central concepts that contribute to this better understanding. Each factor is analyzed and the relationships that favor productivity are established, emphasizing on "Anco" squashes (Butternut type), which are the most cultivated in Argentina.